Cosmic ray intensity variations during the magnetic storm in May 1959 - Manzano, J. R.; Roederer, Juan; Santochi, O. R. (Societa italiana di fisica, 1960)
Fil: Manzano, J. R. Comisión Nacional de Energía Atómica; Argentina